Heritage and the COVID-19 pandemic: the meaning of visitation - Cut Dewi; Matthew Rofe; Julie Nichols; Izziah Izziah (Built Heritage, 2023)
Abstract The onset of the COVID-19 pandemic has impacted global mobility. ‘Lockdowns’ and travel bans have been used as control measures by international governments. Consequently, the ways that we use buildings have also been impacted by these actions. Thus, this paper explores the roles of heritage sites in a post-COVID-19 pandemic society. This research is part of the Urban Heritage and Community Resilience: Conservation, Tourism, and Pandemic project, and it employs methods such as semistructured interviews, participant observations, archival research, and focus group discussions (FGDs). This paper is based on semistructured interviews conducted with one hundred eighteen participants across ten popular heritage sites in Banda Aceh and Aceh Besar, Indonesia. The findings confirm the debated claim in postdisaster studies asserting that some of these Acehnese heritage sites, especially those imbued with religious values, have become places of resilience. Specifically, during the pandemic, these sites have facilitated community resilience by helping people feel closer to God. For practising Acehnese Muslims, prayer at home is culturally acceptable, but praying at the mosque, which is one of the essential heritages of the Acehnese, has contributed to and strengthened the sense of community resilience. Therefore, visitation and participation in heritage sites that include experiencing the sense of place and conducting religious and cultural activities is integral to community resilience.